2004
DOI: 10.1007/s00394-004-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyphenolic extracts from red wine and 4?OH?coumaric acid on 1,2?dimethylhydrazine?induced colon carcinogenesis in rats

Abstract: Total polyphenolic extracts (WE) from red wine, but neither the HMWP nor the LMWP, have some inhibitory effect on the process of colon carcinogenesis by DMH reducing the number of adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Epidemiological studies evaluating the occurrence of polyps after supplementation with vitamin E and β -carotene have yielded mixed results [41], while experimental studies demonstrated protective effects. It has been already shown that vitamin E has antiproliferative properties in cancer cell lines, while different natural antioxidants such as gallic acid [68], polyphenols [69], vitamin D [70], vitamin A [71] pharmacological compounds like bis-1,7-(2-hydroxyphenyl)-hepta-1,6-diene-3,5-dione (BDMCA) [72] have potential to inhibit CRC development in dimethylhydrazine (DMH) model, which is well-established CRC animal model and possesses many characteristics found in human sporadic CRC [73]. …”
Section: Sources Of Free Radicals In Colon: Beneficial Harmful Omentioning
confidence: 99%
“…Epidemiological studies evaluating the occurrence of polyps after supplementation with vitamin E and β -carotene have yielded mixed results [41], while experimental studies demonstrated protective effects. It has been already shown that vitamin E has antiproliferative properties in cancer cell lines, while different natural antioxidants such as gallic acid [68], polyphenols [69], vitamin D [70], vitamin A [71] pharmacological compounds like bis-1,7-(2-hydroxyphenyl)-hepta-1,6-diene-3,5-dione (BDMCA) [72] have potential to inhibit CRC development in dimethylhydrazine (DMH) model, which is well-established CRC animal model and possesses many characteristics found in human sporadic CRC [73]. …”
Section: Sources Of Free Radicals In Colon: Beneficial Harmful Omentioning
confidence: 99%
“…These phenolic compounds exhibit good in vitro antioxidant and chemoprotective properties which may have beneficial effects in vivo [11]. Some naturally occurring phenolic acid and analogues, namely, ferulic acid and gallic acid, are known to display a wide variety of biological functions, in addition to their primary antioxidant activity, which are mainly related to modulation of carcinogenesis [12]. Previous studies in our laboratory have shown that modulation of Phase II antioxidant enzymes and oxidative stress in the liver by phenolic acids may be important events in the protection against adverse effects related to mutagenesis and oxidative damage [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that several polyphenols including PC show potential benefits to human health, such as antioxidant [10], antitumor [11], anti-inflammatory effects [12], and longevity [13], as well as protective effects on glucose consumption [14]. We have also revealed that apple PC showed antiallergy [15], antitumor [16], and antiobesity effects [17] in a rodent model and longevity effects on Caenorhabditis elegans [2].…”
Section: Introductionmentioning
confidence: 99%